A novel protist parasite, Salmoxcellia vastator n. gen., n. sp. (Xcelliidae, Perkinsozoa), infecting farmed salmonids in Norway - Karlsbakk, Egil; Nystøyl, Cecilie Flatnes; Plarre, Heidrun; Nylund, Are (Parasites & vectors, 2021)
In Norway, x-cell parasites associated with disease in farmed salmonids have been known as a rare phenomenon for two decades. These parasites cause systemic infections in farmed rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar), but have so far not been characterized and described. The x-cells from several cases of diseased fish were studied using light and electron microscopy, and by phylogenetic analysis based on small subunit ribosomal RNA (SSU rRNA) gene sequences. We describe here the x-cell parasite as a new species in a new genus, Salmoxcellia vastator n. gen., n. sp. Phylogenetic analyses placed Salmoxcellia n. gen. together with Gadixcellia among the xcelliids, a group of perkinsozoan alveolates. The new genus and species were found to have vacuolate plasmodial x-cells filled with lipid droplets, and an electron-dense alveolar pellicle. Electron-dense cytoplasmic inclusions, which are characteristic of the other xcelliid genera Xcellia and Gadixcellia, are lacking in Salmoxcellia n. gen. These x-cell plasmodia divide by plasmotomy and occur as aggregates in the host tissues, particularly in blood-rich tissues such as those of the kidney, red musculature, heart and liver. Host reaction and the refractive lipid droplets in the x-cells result in S. vastator n. gen., n. sp. aggregates appearing as white patches in the tissues. We describe a new genus and species of xcelliid protist parasites from two very important farmed fish species and provide molecular methods for detection. The new parasite is associated with disease, but more importantly it has a spoiling effect on farmed salmonid fillets, rendering them unsuitable for sale. Consequently, this parasite represents a threat to the aquaculture industry.